Spatio-temporal modeling of carbon stocks and estimated carbon market value across different land covers in Cagayan de Oro River Basin - Tatil, Wella T. (Philippine Journal of Science, 2025)
Effectively addressing the multifaceted challenges posed by climate change in the Cagayan de Oro River Basin necessitates a nuanced understanding of how land cover changes influence carbon stock dynamics. This study aims to assess the spatial distribution and monetary valuation of carbon stock in the river basin, investigating its spatio-temporal dynamics and potential role in climate change mitigation under the REDD+ framework using advanced techniques such as the InVEST tool integrated with geographic information systems and remote sensing. Findings reveal that closed and open forests recorded the highest carbon stock values in the Cagayan de Oro River Basin contributing to 71.92 and 12.57%, respectively, to the basin’s total carbon stock in 2020. The closed forest area expanded by 9,862.83 ha (2010–2020), driving a 53.50% increase in its carbon storage (from 0.87 to 1.34 million Mg ha⁻¹), with projections indicating further growth of 15.59% in area and an 18.47% increase in its carbon storage values by 2030. The total carbon market value in the Cagayan de Oro River Basin is projected to reach PHP 2,258.97 million (USD 40.77 million) by 2030, demonstrating the significant economic potential of conservation efforts. The findings not only underscore the importance of continued environmental preservation but also provide critical insights for policymakers engaged in community-based REDD+ mechanisms in the Philippines. This study advocates for leveraging the development of a robust carbon market in the Philippines to contribute to global climate change mitigation goals and support sustainable land management under the REDD+ framework. It emphasizes the crucial roles of continued government support and community engagement in achieving these objectives.